(untitled) (AYUSHDHARA, 2024)
Kashyap Samhita, provides profound insights into the concept of Aahar (diet) and its significance in maintaining health and preventing diseases. Diet is said to be the cause of stability for sustaining the life of all living beings. Acharya Kashyap in Khila Sthana quotes Aahar as Mahabhaishajyam i.e., no medicine will act as good as food. The person consuming Pathya (congenial) attains health while the one consuming Apathya (non-congenial) is oppressed by illness immediately. Tushti, Pushti, Dhriti, Buddhi, Utsaah, Paurush, Bala, Sausvaryam, Ojas and Tejas are the ideal nutritional markers. According to Ayurvedic dietary concept, different Aahar Kalpana is prescribed for various age groups of children. These formulations are based on factors such as taste, potency, post digestive effects, principles of food combination and timing. This review delves into the approach towards therapeutic aspects of Aahar in managing various ailments and promoting longevity.